Monetary Policy, Leverage, and Bank Risk Taking - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2010)
We provide a theoretical foundation for the claim that prolonged periods of easy monetary conditions increase bank risk taking. The net effect of a monetary policy change on bank monitoring (an inverse measure of risk taking) depends on the balance of three forces: interest rate pass-through, risk shifting, and leverage. When banks can adjust their capital structures, a monetary easing leads to greater leverage and lower monitoring. However, if a bank's capital structure is fixed, the balance depends on the degree of bank capitalization: when facing a policy rate cut, well capitalized banks decrease monitoring, while highly levered banks increase it. Further, the balance of these effects depends on the structure and contestability of the banking industry, and is therefore likely to vary across countries and over time.